Charantin targets HMGCR-PCSK9 axis and activates PPAR-α signaling to ameliorate hyperlipidemia: Mechanistic insights from bioinformatics and in-vivo studies - Ghulam Abbas; Muhammad Nasir Hayat Malik; Haya Yasin; Saud O. Alshammari; Ghulam Murtaza; Waseem Hassan; Muhammad Atif; Ramla Shabbir (PLoS ONE, 2025)
Plant-derived compounds have recently gained attention owing to their better safety profile and multi-targeted actions. Charantin, a plant-based natural compound known for its diverse pharmacological properties, was investigated for its anti-hyperlipdemic activity using both in-silico and in-vivo approaches. A detailed network pharmacology analysis was used to predict charantin-related targets, cross-referenced with hyperlipidemia-associated genes from GeneCards, DisGeNET, and CTD. Shared targets were subjected to protein-protein interaction analysis and functional enrichment using STRING, Cytoscape, and ShinyGO. Molecular docking studies assessed charantin’s binding interactions with key lipid-regulating proteins (HMGCR, PCSK9, LDLR, PPAR-α, PI3K). In-vivo efficacy of charantin (100 and 200 mg/kg) was evaluated in Sprague-Dawley rats fed with high-lipid diet (HLD) for 12 days. Lipid profiles, liver enzymes and transcript levels of lipid-regulating genes were analyzed. A total of 242 overlapping genes were identified between charantin targets and hyperlipidemia-associated genes, with enrichment analyses highlighting key lipid metabolic and inflammatory pathways. Molecular docking revealed that charantin exhibited stronger binding affinities than simvastatin across multiple targets. In HLD animal model, charantin significantly reduced total cholesterol, triglycerides, LDL, and VLDL, while increasing HDL levels in a dose-dependent manner. Liver function remained preserved, accompanied by downregulation of HMGCR, PCSK9, and APOB, and upregulation of LDLR and PPAR-α at both gene and protein levels. Charantin exerts potent lipid-lowering effects through modulation of multiple pathways, including cholesterol biosynthesis, lipoprotein metabolism, and nuclear receptor activation. Its efficacy and hepatoprotective properties reiterate its potential as a safe, effective alternative or adjunct to conventional therapies for hyperlipidemia.